Security issues of Vehicular Ad Hoc Networks (VANET): A Systematic Review - Sahabdeen Aysha Asra (TIERS Information Technology Journal, 2022)
Vehicular ad hoc networks (VANETs) are a subset of mobile ad hoc networks (MANETs) that refer to a group of connected cars. The various networking layers in common Internet protocol stack topologies are linked to security vulnerabilities in VANETs. A security breach in a VANET is typically serious and harmful. Also Current VANET security standards handle the bulk of the security issues that vehicle networks confront. This paper presents VANET’s different types of security attacks in a systematic review approach. The information was gathered by a systematic examination of existing research articles. Furthermore, the study's shortcomings were the dataset's size and the absence of quality characteristics.